BIOGAS SEBAGAI MODEL MITIGASI EMISI GAS METAN PADA SEKTOR PETERNAKAN DI PROVINSI RIAU - Eka Rahma Citra Lestari; Usman M Tang; Bintal Amin (Jurnal Ilmu Lingkungan, 2013)
This study aims to determine the amount of methane gas emissions generated from thelivestock sector in Riau Province in 2007-2011 and to analyze biogas as a mitigation modelto reduce the emission of methane gas. Mitigation model was based on the institutional,community, breeders, technical and environmental aspects by using the Analytical Hierarchy Process (AHP). The results of this study showed that the largest source of methane emissionscome from livestock of beef cattle, amounting to 8275 tonnes in 2011. Based on thecalculation of AHP, the mitigation model of biogas could be made by prioritizingenvironmental aspects, which include improving environmental sanitation, reduce odorpollution, reduce greenhouse gases, and helps forest, land and water conservation programs.